دراسة التفكك الحيوي لسلفونات ألكيل البنزن الخطية LAS (Latakia University Journal -Basic Sciences Series, 2016)
تعد سلفونات ألكيل البنزن الخطية  LAS من الملوثات العضوية الناجمة عن استخدام المنظفات بأصنافها. وقد  أجريت دراسات متعددة حول حوض البحر الأبيض المتوسط لمراقبة تراكيز هذه الملوثات، إلا أنه قليلا ما هو معروف حول مصيرها البيئي، وتأثير العوامل البيئية على تحلل هذه المركبات. تم في هذا البحث إجراء دراسة مخبرية لتفكك مركبات سلفونات ألكيل البنزن الخطية تحت شروط مختلفة، خلال الفترة الممتدة من أيلول إلى كانون الأول عام 2007   استمرت فترة الحضن لمدة  ثلاثة أشهر، حيث وضعت العينات في شروط مختلفة (شروط مخبرية بوجود الضوء، شروط مخبرية بمعزل عن الضوء عند C°25 وC°15)  تم تحديد التركيز الكلي لمركبات LAS والمواصفات الهيدرولوجية وفق البرنامج الزمني الآتي: (90-60-45-30-21-14-7-5-3-1-0) يوم ، أظهرت التجارب انخفاض التركيز الكلي لمركبات LAS مع مرور زمن الحضن بنسب تفكك مختلفة, رافق ذلك تغير المواصفات الهيدرولوجية للمياه بفعل التفكك الحيوي، وعمليات التركيب الضوئي الجارية في الوسط المائي. The linear alkyl benzene sulfonate is organic pollutants resulting from uses of detergents types. I have conducted several studies on the Mediterranean to monitor the concentrations of these pollutants, however, little is known about the fate of the environment and the effect of environmental factors on the degradation these compounds. In this research laboratory to conduct a study of the degradation of alkyl benzene sulfonate compounds  under different conditions, during the period from September to November 2007 period cuddling continued for three months, and storage the samples in different conditions, (Laboratory conditions presence of light, laboratory conditions in  isolation from the light at  25 C° and 15 C°) were identified in total concentration of LAS hydrological and specifications according to the following program:(0-1-3-5-7-14-21-30-45-60-90) day. The results showed decrease total concentration of compounds LAS  with the passage of time cuddling, compounds change specifications hydrological water by the biodegradation of the vital processes of  photosynthesis taking place in aqueous media.